SUB CHRONIC AND ACUTE TOXICITY OF LAUNDRY DETERGENT WASTE FISH FRY PATIN (Pangasius hypophthalmus) - Paiturrahman Sirait; Saberina Hasibuan; Syafriadiman Syafriadiman (Berkala Perikanan Terubuk, 2020)
Laundry activities produce waste laundry detergent. Laundry detergent waste toxicity tests need to be done research on test animals Patin (P. hypophthalmus) to determine the effect of surfactant materials on water quality and fish mortality rate Patin. This study aims to get the effect of acute and sub-chronic toxicity of waste and get the laundry detergent safe doses for seed growth Patin. The method used in this study is an experimental method by using a completely randomized design (CRD) with four treatments and three replications of each treatment. Preliminary test results obtained under the threshold value of 100 ml/L and the threshold value above 1000 ml/L. Acute toxicity tests using probit anlisis LC50-96 values obtained laundry detergent waste hours on 397 ml/L. In sub-chronic toxicity test showed the best concentration of laundry detergent waste contained at a concentration of 3.97 ml/L with an absolute weight of 1.15 grams, specific growth rate of 1.48% and 90% fish survival. Value safe biological limits in this study was 3.97 ml/L. It can be concluded that the difference in concentrations of laundry detergent waste significant effect (p<0.05) to Patin. The concentration of 3.97 ml/L is safe and not harmful to the aquaculture process Patin (P. hypophthalmus) using common water resources.